Sosialisasi dan Pelatihan Pembuatan Kue Putu Ayu dalam Upaya Meningkatkan Ekonomi Masyarakat Desa - Rahmiati, Baiq Fitria; Naktiany, Wayan Canny; Lastyana, Wiwin; Yunita, Lina; Solehah, Novia Zuriatun; Sukanthy, Ni Made Wiasty; Dewi, Novianty Tysmala (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Gemel Village is one of the areas in Central Lombok. Most of the women in Gemel Village are housewives. There is no extra income for them. So the team of Bumigora university lecturers wanted to help improve the economy in Gemel village. The training and assistance in making Putu Ayu Cake was carried out for the underprivileged community in Bunprie, Gemel Village. The Cake Making Training was held on June 19, 2021. The participants who took part in the training were 30 people from underprivileged women in Bunprie. The training took place at the house of the Head of Bunprie. community service activities for lecturers and students at Bumigora University went well and received good appreciation and attention from the target community. Then it is hoped that the socialization and training can lead to changes in behavior so that the resulting product can help the economy of the target community.